Lithium magnesium nitrogen hydrogen material coated by polymer chemical linking and preparation method thereof

By using polymer chemical link coating technology on lithium magnesium nitrogen hydrogen materials, borohydride reacts with metal hydride and ammonium to form an ester-based polymer shell layer, the problems of high hydrogen absorption and release of materials and fast attenuation of hydrogen storage capacity are solved, and more efficient hydrogen storage and release are achieved.

CN117303308BActive Publication Date: 2025-03-07CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311547800.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2025-03-07
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

The temperature required for lithium-magnesium nitrogen hydrogen materials during hydrogen absorption and discharge is high, and the hydrogen storage capacity decays quickly after recycling, which cannot meet the needs of energy storage and transportation fields.

Method used

The lithium-magnesium nitrogen hydrogen material coated with polymer chemical links is used to react with the metal hydride and metal amide in the core layer through borohydride as a linking molecule to form a polymer shell layer containing an ester group, which is uniformly coated outside the core layer to reduce the agglomeration and fusion of nanoparticles.

Benefits of technology

The hydrogen absorption and release temperature of lithium-magnesium nitrogen hydrogen materials is reduced, the cycle life is extended, the hydrogen storage capacity is maintained, and the hydrogen absorption and release rate is increased through catalytic action.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117303308B_ABST
    Figure CN117303308B_ABST
Patent Text Reader

Abstract

The invention discloses a lithium magnesium nitrogen hydrogen material coated by polymer chemical linking and a preparation method thereof, belonging to the field of solid-state hydrogen storage. The composite material comprises a core layer and a polymer shell layer, the raw materials of the core layer comprise metal hydride, metal amide and borohydride, the polymer shell layer is a polymer containing an ester group, borohydride is used as a linking molecule, the linking molecule is distributed on the core layer, O in the polymer shell layer -O-R can form a B-O bond with the borohydride, the core layer and the polymer shell layer have a strong bonding force, so that the polymer shell layer can be uniformly coated outside the core layer, a small amount of substrate can be used to form a good barrier for LMNH particles, thereby reducing the degradation of the hydrogen storage capacity per unit mass, and a relatively high hydrogen storage capacity can be maintained after multiple hydrogen charging and discharging cycles; at the same time, the borohydride can be used as a catalyst for the reaction of the LMNH material with hydrogen, accelerate the reaction rate of the metal amide-hydride, thereby improving the LMNH hydrogen absorption and desorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium magnesium nitrogen hydrogen material coated by polymer chemical linking and a preparation method thereof, belonging to the field of solid-state hydrogen storage. Background Art

[0002] High-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage and solid-state hydrogen storage are the three mainstream hydrogen storage technologies at present. Compared with high-pressure gaseous and low-temperature liquid hydrogen storage technologies that use the physical properties of hydrogen to achieve hydrogen storage, solid-state hydrogen storage technology mainly relies on specific hydrogen storage materials to achieve hydrogen storage. According to the different ways of interaction with hydrogen, hydrogen storage materials can be divided into physical hydrogen storage and chemical hydrogen storage materials. Physical hydrogen storage materials are mainly some porous materials with large specific surface area and complex pore structure, such as activated carbon, carbon nanotubes, graphene, MOFs, etc. This type of material mainly achieves H2 adsorption through the van der Waals force between the material and H2. However, due to the low intensity of the van der Waals force, physical hydrogen storage materials generally have an ideal hydrogen storage capacity at extremely low temperatures (such as 77K temperature of liquid nitrogen), which is not suitable for practical applications. Chemical hydrogen storage materials store H2 by chemically reacting with H2 to form hydrogen-containing compounds. The reaction temperature is generally between room temperature and a certain high temperature range (≤400°C). Compared with physical hydrogen storage materials, they are more practical. Therefore, the current research on solid hydrogen storage materials at home and abroad is mainly focused on chemical hydrogen storage materials. At present, common hydrogen storage materials are mainly hydrogen storage alloys, including rare earth AB5 type, titanium iron AB type and titanium manganese AB2 type. The above solid hydrogen storage alloys have achieved a certain scale of commercialization and demonstration applications due to their advantages such as high volume hydrogen storage density, high hydrogen release purity, low hydrogen charging pressure and high intrinsic safety. However, hydrogen storage alloys are often limited to a relatively low mass hydrogen storage density of less than 2wt%, and cannot fully meet the requirements for hydrogen storage in application scenarios such as hydrogen energy storage and hydrogen energy transportation.

[0003] A series of lightweight composite hydrogen storage materials composed of light elements have a theoretical mass hydrogen storage density of up to 5.5 wt%-21wt%, bringing hope for technological breakthroughs in solid-state hydrogen storage materials. Representative materials include NaAlH4 complex hydride system, LiBH4 borohydride system, MgH2 magnesium-based hydride system, etc. However, most of these materials do not have the possibility of commercial application due to the need for hydrogen charging and discharging at high temperatures above 300°C, no reversible cyclicity, or rapid cyclic decay of hydrogen storage capacity. Another type of composite hydride system represented by metal amide-metal hydride has avoided the above defects to a certain extent. The representative material lithium magnesium nitrogen hydride (Li-Mg-NH, prepared by mixing Mg(NH2)2-LiH or LiNH2-MgH2 in different proportions, and written as LMNH unless otherwise specified in the present invention) has a high hydrogen storage capacity of 5.6wt%. Theoretically, the hydrogen desorption temperature is as low as 90°C under a hydrogen pressure of 0.1 MPa (almost the same as the operating conditions of vehicle-mounted proton exchange membrane fuel cells), and the hydrogen charging and discharging are completely reversible. It is considered to be the next generation solid-state hydrogen storage material with the greatest commercial potential.

[0004] However, the material currently has defects such as high temperatures required for actual hydrogen absorption and desorption (≥180°C) and rapid decay of hydrogen storage capacity after multiple cycles of use, which cannot meet the needs of energy storage, transportation and other fields. Existing research shows that the technical means to address the defect of high temperatures required for material hydrogen absorption and desorption is to reduce the particle size of the material while adding a suitable catalyst. Reducing the particle size can effectively shorten the mass transfer distance in the solid-phase hydrogen absorption and desorption reaction, while reducing the reaction kinetic energy barrier. In terms of adding catalysts, some catalysts can reduce the thermodynamic stability of amino reactants (by destroying the stability of metal-N bonds or NH bonds), allowing the reaction to proceed under milder conditions; some catalysts have higher Li + Conductivity, further accelerating the solid phase reaction rate. By extending the mechanical milling time or using high-energy ball milling methods, the LMNH particle size is effectively reduced to the range of 100 nanometers to 200 nanometers. The temperature of LMNH materials with nano-scale particles to fully absorb and desorb hydrogen can be as low as 130°C [1] The commonly used catalysts for LMNH are mainly alkali metal compounds, such as KH, KOH, RbH, CsH; carbon-based or metal-carbon-based composites, such as carbon nanotubes (CNT), Ru@graphene (in the present invention, unless otherwise specified, A@B means A is coated on the surface of B); metals, metal oxides or metal halides, such as Ti, TiO2, V, V2O5, VCl3, TiCl3, ScCl3, NiCl2, etc.; metal amides or bimetallic hydrides, such as K2Mn(NH2)4, Li3AlH6, NaAlH4, etc. [2-6]. The temperature of the fully absorbed and desorbed hydrogen of the catalytically modified LMNH material can be further reduced to 110°C. However, the nano-LMNH particles synthesized by ball milling usually have a higher surface energy (the catalytically improved LMNH is also prepared by mechanical ball milling). The LMNH materials with high surface energy tend to undergo particle fusion, agglomeration and regrowth due to the spontaneous reduction of surface energy during the hydrogen absorption and desorption cycle. For example, after the LMNH with a particle size range of 100nm-200nm is charged with hydrogen twice, its particle size increases from 100nm-200nm to 700nm-800nm. The hydrogen absorption and desorption performance also decreases rapidly with the increase of the LMNH particle size. At present, the reversible hydrogen storage capacity of nano-LMNH and its catalytically modified products has only undergone a few cycles of hydrogen absorption and desorption, and the attenuation is greater than 15%, which makes it almost impossible to commercialize.

[0005] In order to solve the problem of LMNH's rapid cycle performance degradation, the current solution includes coating and confinement of LMNH. The coating method is to use organic substances such as triphenyl phosphate (TPP) [7] 、Poly (4-methyl-1-pentene) (TPX) [8] Acting as a substrate, LMNH nanoparticles are coated in it during the ball milling process, so that the organic matter acts as a buffer layer to limit the contact and fusion of nanoparticles during the organic matter@LMNH cycle. The confinement rule is to dissolve Mg(NH2)2 and LiH precursors such as n-butyl magnesium, lithium nitride, etc. in the corresponding solvent and introduce them into the substrate, such as carbon nanofibers or thin hollow carbon spheres, and then heat-treat and reduce them in a hydrogen atmosphere to obtain the substrate@LMNH [9-11] These technical means can improve the cycle life of LMNH materials to a certain extent, but there are still the following defects: the substrate used to separate LMNH nanoparticles is overdoped, and the substrate does not participate in hydrogen absorption and desorption, which is equivalent to the total hydrogen storage capacity of LMNH remaining unchanged, but the mass is greatly increased, making the hydrogen storage capacity of LMNH composite materials less than 3wt%.

[0006] Therefore, it is crucial for the commercialization of LMNH to provide an effective technical means to reduce the hydrogen absorption and desorption temperature of LMNH while hindering the agglomeration, fusion, and regrowth of nano-LMNH during the cycle, improve its performance stability during long-term operation, and maintain the high hydrogen storage capacity of the original material. Summary of the invention

[0007] In order to overcome the shortcomings of the prior art, the present invention provides a lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage and a preparation method thereof, which can coat LMNH and prevent LMNH nanoparticle fusion while minimizing the amount of substrate used and reducing the degradation of hydrogen storage capacity per unit mass.

[0008] The technical solution adopted by the present invention to solve its technical problem is:

[0009] In a first aspect, the present application provides a lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage, comprising a core layer and a polymer shell layer, wherein the raw materials of the core layer include metal hydride, metal amide and borohydride, wherein the metal ion of one of the metal hydride and the metal amide is lithium, and the metal ion of the other is magnesium, and the polymer shell layer is a polymer containing an ester group.

[0010] The polymer-coated lithium magnesium nitrogen hydrogen material provided in the present application uses borohydride as a linking molecule, and the linking molecule is distributed in the core layer. In the ester group of the polymer shell, the O in -OR (R refers to a non-hydrogen group such as an alkyl group) can form a BO bond with B in the borohydride. The core layer and the polymer shell have a strong bonding force, so that the polymer shell can be evenly coated outside the core layer. Under the premise of forming the same barrier degree for LMNH particles, a smaller amount of substrate can be used than the prior art, thereby reducing the degradation of the hydrogen storage capacity per unit mass; at the same time, the borohydride can be used as a catalyst for the reaction of the LMNH material with hydrogen, accelerating the reaction rate of the metal amide-hydride, thereby increasing the hydrogen absorption and desorption rate of LMNH.

[0011] Furthermore, in the raw materials of the core layer, the amount of the borohydride used is 1%-15% of the total amount of magnesium in both the metal hydride and the metal amide, calculated on a substance basis.

[0012] If the borohydride doping amount is insufficient, the bonding force between the core layer and the polymer shell layer will not be significantly enhanced, which is not conducive to the uniform distribution of the polymer material on the surface of the core layer, and the catalytic effect is also poor; if the borohydride doping amount is too much, the hydrogen desorption temperature of the composite material will be increased, reducing the material performance.

[0013] Furthermore, the particle size of the core layer is in the range of 10nm-2000nm, and the mass of the polymer shell layer is 2%-15% of the mass of the core layer. After adding a suitable amount of borohydride to the core layer, the self-stacking of the polymer shell layer can be effectively reduced, and even if a relatively small proportion of the polymer shell layer is used, the hydrogen storage capacity decay of the composite material can still be reduced after multiple hydrogen absorption and desorption.

[0014] Furthermore, the mass of the polymer shell is 3%-7% of the total mass of the metal hydride and the metal amide.

[0015] Further, the borohydride is selected from LiBH4, KBH4, NaBH4, Be(BH4)2, Mg(BH4)2, Ca(BH4)2, Al(BH4)3, LiK(BH4)2, LiY(BH4)4, NaY(BH4)4, LiZn2(BH4)5, NaZn2(BH4)5, Li3MZn5(BH4) 15, KZn(BH4)Cl2, NaY(BH4)Cl2, LiX(BH4)3Cl, LiLa(BH4)3Br, LiLa(BH4)3I, Li(BH4) 1-x Q x 、Na(BH4) 1-x Q x 、K(BH4) 1-x Q x 、Ca((BH4) 1-x Q x )2, Li2(BH4)(NH2), Li4(BH4)(NH2)3, Na2(BH4)(NH2), Mg(BH4)(NH2), A(BH4) g •nNH3, LiMg(BH4)3•nNH3, Li2Mg(BH4)4•nNH3, Li2Al(BH4)5•nNH3, LiSc(BH4)4•nNH3, Li2Mn(BH4)4•nNH3, Li2Fe(BH4)5•nNH3 or NaZn(BH4)3•nNH3;

[0016] Where: 0≤x≤1; M=Mg or Mn; X=La, Ce, Pr, Nd, Sm or Gd; Q=Cl, Br or I; A=Li, Mg, Ca, Sr, Al, V, Cr, Mn, Fe, Co, Zn, Y, Zr, La, Ce, Gd or Dy, the value of g is equal to the valence of the corresponding metal ion of A; n=1, 2, 3, 4, 5 or 6.

[0017] This type of compound plays two main roles in the system. First, as a catalyst, borohydride is first of all a type of solid electrolyte with lithium ion conductivity. Some borohydrides have a lithium ion conductivity of 10 at room temperature. -3 S / cm-10 -4 S / cm, and its lithium ion conductivity can be further increased to 10 at the common operating temperature of LMNH (150°C-190°C). -2 S / cm level, the high lithium ion conductivity of borohydride makes Li + It can be quickly transferred in the LMNH solid phase, accelerating the reaction rate of metal amide-hydride, thereby increasing the hydrogen absorption and desorption rate of LMNH; in addition, borohydride can effectively destroy the metal-N or NH bond in the metal amide and form a (BH4) - and (NH2) - The intermediate of ions has lower thermodynamic stability than metal amides, so it is easier to react with metal hydrides than metal amides, thereby reducing the LMNH reaction energy barrier and allowing the reaction to proceed at a lower temperature. -The boron element in LMNH can interact with the oxygen element in the ester group of the polymer shell to form a BO bond. Therefore, when the borohydride is evenly dispersed in LMNH, the polymer containing the ester group can form a uniform coating on the surface of LMNH. And because it is a chemical bond connection rather than a simple physical coating, the polymer is firmly connected to the surface of LMNH and will not shift or fall off during the hydrogen absorption and desorption cycle.

[0018] Furthermore, the material of the polymer shell layer is selected from at least one of polymethyl methacrylate, polycarbonate, polycaprolactone, polyurethane, polyethylene terephthalate, polybutylene terephthalate, polyarylate, polyphenylene terephthalate-butylene terephthalate, and polylactic acid polyester, or is selected from a composite polymer containing an ester structure on the polymer chain segment.

[0019] Furthermore, the molecular weight of the material of the polymer shell layer is in the range of 20,000-500,000, which is convenient for preparing the polymer solution in the process of preparing the composite material and avoids melting at the common working temperature of LMNH.

[0020] In a second aspect, the present application provides a method for preparing a lithium magnesium nitrogen hydrogen material coated by polymer chemical linking, comprising the following steps:

[0021] In a protective atmosphere, metal hydride, metal amide and borohydride are mixed and ball-milled to obtain a core layer; the metal ion of one of the metal hydride and the metal amide is lithium, and the metal ion of the other is magnesium;

[0022] In a protective atmosphere, a polymer containing an ester group is added to an organic solvent to prepare a completely dissolved polymer solution;

[0023] The core layer is added to the polymer solution, stirred and aged, and then volatilized in a vacuum environment to remove the organic solvent, thereby obtaining the lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage.

[0024] Ball milling allows the borohydride as a linking molecule to be evenly distributed inside and on the surface of the core layer. In addition to forming a BO bond through the interaction between the B element and the O element of the -OR ester group in the polymer, first preparing the polymer solution and then gradually evaporating the solvent is more conducive to full contact between the polymer substrate and the core layer, and more conducive to the formation of a uniform coating of the core layer by the polymer.

[0025] Further, the organic solvent is selected from methanol, ethanol, propanol, isopropanol, butanol, isobutanol, cyclopentanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 4-methylcyclohexanol, glycerol, benzyl alcohol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, methyl ether, ethyl ether, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, tetrahydrofuran, 2-methylfuran, 3-methylfuran , 2,5-dimethylfuran, 2-methyltetrahydrofuran, acetone, methylacetone, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylpropionamide, N,N-dimethylacetamide, N-ethylacetamide, 2-pyrrolidone, N-methylpyrrolidone, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, butylcyclohexane, toluene, xylene, m-xylene, p-xylene, xylene, ethylbenzene, diethylbenzene, dichloromethane, chloroform or carbon tetrachloride.

[0026] Furthermore, the concentration of the polymer solution is 5 mg / ml-100 mg / ml.

[0027] The beneficial effects of the present invention are as follows: the present invention uses borohydride as a linking molecule, the linking molecule is distributed on the core layer, the O in the ester group -OR of the polymer shell layer can form a BO bond with B in the borohydride, the core layer and the polymer shell layer have a strong bonding force, so that the polymer shell layer can be evenly coated outside the core layer, and a small amount of substrate can be used to form a good barrier for LMNH particles, thereby reducing the degradation of the hydrogen storage capacity per unit mass, and a relatively high hydrogen storage capacity can be maintained after multiple hydrogen charging and discharging cycles; at the same time, the borohydride can be used as a catalyst for the reaction of the LMNH material with hydrogen, accelerating the reaction rate of the metal amide-hydride, thereby improving the hydrogen absorption and desorption rate of the LMNH.

[0028] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained by the structures particularly pointed out in the written description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is the XRD pattern of LMNH and PMMA@LMNH-CB.

[0030] Figure 2 It is the XRD pattern of LMNH and PC@LMNH-LB.

[0031] Figure 3 It is the XRD pattern of LMNH and PMMA@LMNH-LAB.

[0032] Figure 4 This is the FTIR spectrum of PMMA@LMNH-CB.

[0033] Figure 5 yes Figure 4 1315 -1 -1415 cm -1 Zoomed in view of the range.

[0034] Figure 6 This is the FTIR spectrum of PC@LMNH-LB. The inner figure is for 1315 -1 -1415 cm -1 A magnified display of the range.

[0035] Figure 7 This is the FTIR spectrum of PMMA@LMNH-LAB. The inner figure is the spectrum of 1315 -1 -1415 cm -1 A magnified display of the range.

[0036] Figure 8 It is a comparison diagram of isothermal hydrogen absorption curves of Example 2, PC@LMNH, and PC@LMNH-KH at different temperatures.

[0037] Fig. 9 It is a comparison diagram of isothermal hydrogen desorption curves of Example 2, PC@LMNH, and PC@LMNH-KH at different temperatures.

[0038] Fig.10 This is the hydrogen absorption and desorption cycle curve of pure LMNH material.

[0039] Fig.11 This is the hydrogen absorption and desorption cycle curve of PMMA@LMNH-CB.

[0040] Fig.12 This is the hydrogen absorption and desorption cycle curve of PC@LMNH-LB.

[0041] Fig.13 Hydrogen absorption and desorption cycle curve of PMMA@LMNH-LAB. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings of the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] It should be understood that, under the premise of no conflict, any and all embodiments of the present invention can be combined with the technical features in any other embodiment or multiple other embodiments to obtain another embodiment. The present invention includes such a combination to obtain another embodiment.

[0044] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.

[0045] It should be understood that the singular forms used in the present invention, such as "a", include plural references unless otherwise specified. In addition, the term "comprising" is an open limitation and not a closed form, that is, including the contents specified in the present invention, but not excluding other aspects.

[0046] In the prior art, when a substrate is used to coat LMNH materials, the bonding force between the substrate and the LMNH materials is not strong. Due to similar compatibility, the substrate is more inclined to stack on itself, so it is difficult for the substrate to be uniformly coated on the surface of the LMNH material. This results in the same LMNH particle having a thick substrate in some positions and no substrate in some positions. The positions without substrate are easy to agglomerate and fuse with other LMNH particles that are also poorly coated in the high temperature of hydrogen absorption and desorption. This is one of the reasons why even if the LMNH material is coated, there will still be a certain decrease in hydrogen storage capacity after hydrogen absorption and desorption. In order to minimize the decrease in hydrogen storage capacity due to this reason, it is generally necessary to use more substrates, but the substrate will not react with hydrogen, resulting in a significant decrease in the hydrogen storage capacity per unit mass of the composite material.

[0047] In view of the above problems, the present invention provides a method for preparing a lithium magnesium nitrogen hydrogen material coated with a polymer chemical link, comprising the following steps:

[0048] S1: In a protective atmosphere, metal hydride, metal amide and borohydride are mixed and ball-milled to obtain a core layer. The metal ion of one of the metal hydride and the metal amide is lithium, and the metal ion of the other is magnesium.

[0049] S2: In a protective atmosphere, the ester-containing polymer is added to an organic solvent to prepare a completely dissolved polymer solution.

[0050] S3: adding the core layer to the polymer solution, stirring and aging, and then volatilizing in a vacuum environment to remove the organic solvent, thereby obtaining a lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage.

[0051] Step S1 can make the borohydride evenly dispersed in the core layer. Borohydride itself is a hydrogen storage material, which can store and release hydrogen together with LMNH. Step S2 is made into a polymer solution to facilitate the uniform dispersion of the core layer in the polymer solution in step S3, avoiding random stacking like physical deposition method, and then the O in -OR in the ester group of the polymer shell forms a BO bond with B in the borohydride. The core layer and the polymer shell are connected by chemical bonds, so that the polymer shell can be evenly coated on the outside of the core layer. Under the premise of forming the same barrier degree for LMNH particles, less substrate can be used than the prior art, thereby reducing the degradation of hydrogen storage capacity per unit mass.

[0052] The lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage thus prepared includes a core layer and a polymer shell layer. The raw materials of the core layer include metal hydride, metal amide and borohydride. The metal ion of one of the metal hydride and the metal amide is lithium, and the metal ion of the other is magnesium. The polymer shell layer is a polymer containing an ester group.

[0053] Since the core layer can be coated with a thin and uniform polymer shell, the LMNH material is not easy to fuse, and the hydrogen storage capacity decreases less after multiple hydrogen absorption and desorption. In addition, borohydride acts as a catalyst for the reaction between LMNH material and hydrogen, accelerating the reaction rate of metal amide-hydride, thereby increasing the hydrogen absorption and desorption rate of LMNH.

[0054] Regarding the selection of metal hydride and metal amide, specifically it can be a combination of LiNH2 and MgH2, or a combination of Mg(NH2)2 and LiH. The molar ratio of Mg to Li elements in the metal hydride and the metal amide is 1:1, 1:2, 1:3, 1:4, 2:3, 2:5, 2:7, 3:5, 3:7, 3:8, etc., and 1:2 or 3:8 is particularly preferred. The inventors have found that when the molar ratio of Mg to Li atoms is 1:2, that is, the composition contains Mg(NH2)2-2LiH or MgH2-2LiNH2, the composite material exhibits good performance in hydrogen storage capacity and hydrogen absorption and desorption rate.

[0055] Boron hydride refers to a compound containing (BH4) - Ionic compounds, preferably selected from LiBH4, KBH4, NaBH4, Be(BH4)2, Mg(BH4)2, Ca(BH4)2, Al(BH4)3, LiK(BH4)2, LiY(BH4)4, NaY(BH4)4, LiZn2(BH4)5, NaZn2(BH4)5, Li3MZn5(BH4) 15 , KZn(BH4)Cl2, NaY(BH4)Cl2, LiX(BH4)3Cl, LiLa(BH4)3Br, LiLa(BH4)3I, Li(BH4) 1-x Qx 、Na(BH4) 1-x Q x 、K(BH4) 1-x Q x 、Ca((BH4) 1-x Q x )2, Li2(BH4)(NH2), Li4(BH4)(NH2)3, Na2(BH4)(NH2), Mg(BH4)(NH2), A(BH4) g •nNH3, LiMg(BH4)3•nNH3, Li2Mg(BH4)4•nNH3, Li2Al(BH4)5•nNH3, LiSc(BH4)4•nNH3, Li2Mn(BH4)4•nNH3, Li2Fe(BH4)5•nNH3 or NaZn(BH4)3•nNH3;

[0056] Where: 0≤x≤1; M=Mg or Mn; X=La, Ce, Pr, Nd, Sm or Gd; Q=Cl, Br or I; A=Li, Mg, Ca, Sr, Al, V, Cr, Mn, Fe, Co, Zn, Y, Zr, La, Ce, Gd or Dy, the value of g is equal to the valence of the corresponding metal ion of A; n=1, 2, 3, 4, 5 or 6.

[0057] This type of compound plays two main roles in the system. First, as a catalyst, borohydride is first of all a type of solid electrolyte with lithium ion conductivity. Some borohydrides have a lithium ion conductivity of 10 at room temperature. -3 S / cm-10 -4 S / cm, and its lithium ion conductivity can be further increased to 10 at the common operating temperature of LMNH (150°C-190°C). -2 S / cm level, the high lithium ion conductivity of borohydride makes Li + It can be quickly transferred in the LMNH solid phase, accelerating the reaction rate of metal amide-hydride, thereby increasing the hydrogen absorption and desorption rate of LMNH; in addition, borohydride can effectively destroy the metal-N or NH bond in the metal amide and form a (BH4) - and (NH2) - The intermediate of ions has lower thermodynamic stability than metal amides, so it is easier to react with metal hydrides than metal amides, thereby reducing the LMNH reaction energy barrier and allowing the reaction to proceed at a lower temperature. -The boron element in LMNH can interact with the oxygen element in the ester group of the polymer shell to form a BO bond. Therefore, when the borohydride is evenly dispersed in LMNH, the polymer containing the ester group can form a uniform coating on the surface of LMNH. And because it is a chemical bond connection rather than a simple physical coating, the polymer is firmly connected to the surface of LMNH and will not shift or fall off during the hydrogen absorption and desorption cycle.

[0058] If the amount of borohydride doping is insufficient, the bonding force between the core layer and the polymer shell layer will not be significantly enhanced, which is not conducive to the uniform distribution of the polymer material on the surface of the core layer, and the catalytic effect is also poor; if the amount of borohydride doping is too much, the hydrogen release temperature of the composite material will be increased, reducing the material performance. For example, LiBH4 itself is also a hydrogen storage material, but its full hydrogen release temperature is close to 400°C; for example, the composite material with a molar ratio of LiNH2:LiBH4:MgH2=2:1:1 has a hydrogen release amount of only 3.0wt% (within 30min) at 180°C. Preferably, in the raw materials of the core layer, the amount of borohydride used is 1%-15% of the magnesium element contained in the metal hydride plus the metal amide, which is beneficial to ensure the connection effect between the core layer and the polymer shell layer, maintain the working temperature of the composite material at a low level, and ensure that the composite material has a mass hydrogen storage density close to that of pure LMNH particles.

[0059] The polymer carrier (the material of the polymer shell) plays the role of coating the core layer during the synthesis. This coating physically isolates the LMNH nanoparticles containing borohydride, inhibits the contact, fusion, agglomeration and regrowth of the nanoparticles during the subsequent long-term hydrogen absorption and desorption of the composite material, and effectively improves the long-term performance stability of the composite material. The polymer material containing an ester group is preferably selected from at least one of polymethyl methacrylate (PMMA), polycarbonate (PC), polycaprolactone (PCL), polyurethane (PU), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyarylate (PAR), polyphenylene terephthalate (PTT), polylactic acid polyester (PGA), or is selected from a composite polymer containing an ester structure on the polymer chain segment.

[0060] The molecular weight of the polymer carrier is preferably in the range of 20000-500000. If the molecular weight is too low, it is easy to melt in the high temperature of hydrogen absorption and desorption, weakening the coating effect. If the molecular weight is too high, it is difficult to prepare a completely dissolved polymer solution, which is not conducive to uniform coating of the core layer.

[0061] The particle size range of the core layer is 10nm-2000nm, and the mass of the polymer shell layer is 2%-15% of the mass of the core layer. It is preferably 3wt%-15wt% of the total mass of the metal hydride and the metal amide, and the more preferred amount of addition should be 3wt%-7wt% of the total mass of the metal hydride and the metal amide. In order to make the core layer reach this particle size range, in step S1, a planetary ball mill is used for mechanical ball milling, the raw material is mixed with ball milling steel balls, the ball-to-material ratio is 20-100, the rotation speed is 150 rpm-500 rpm, and the ball milling time is 12 h-48h. The mixing and ball milling processes are all carried out in an argon atmosphere, and the water and O2 contents are <0.01ppm.

[0062] Since LMNH is sensitive to water and oxygen, an anhydrous organic solvent is required as the solvent. The organic solvent is selected from methanol, ethanol, propanol, isopropanol, butanol, isobutanol, cyclopentanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 4-methylcyclohexanol, glycerol, benzyl alcohol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, methyl ether, ethyl ether, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, tetrahydrofuran, 2-methylfuran, 3-methylfuran, 2,5 - dimethylfuran, 2-methyltetrahydrofuran, acetone, methylacetone, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylpropionamide, N,N-dimethylacetamide, N-ethylacetamide, 2-pyrrolidone, N-methylpyrrolidone, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, butylcyclohexane, toluene, o-xylene, m-xylene, p-xylene, xylene, ethylbenzene, diethylbenzene, dichloromethane, chloroform or carbon tetrachloride.

[0063] The polymer forms a polymer solution with a concentration of 0.005 g / ml-0.1 g / ml, preferably 0.01 g / ml-0.05 g / ml, so as to obtain a suitable viscosity to disperse the core layer therein, and the organic solvent can be evaporated quickly in step S3.

[0064] Step S2 is specifically to add the selected polymer to the corresponding organic solvent, and stir for 1h-3h under argon atmosphere (water, O2 content <0.01ppm), 100rpm-500rpm, 25℃-85℃, to obtain a clear solution in which the polymer is completely dissolved. Step S3 is specifically to continue stirring the mixed slurry at 100rpm-500rpm, 25℃-85℃ for 1h-3h, and ageing for 4h-48h; placing the aged mixed slurry in a vacuum environment, drying at 25℃-150℃, removing the organic solvent, and the drying time is 2h-24h.

[0065] Example 1

[0066] LiNH2 and MgH2 are used as raw materials, calcium borohydride (Ca(BH4)2) is used as a catalyst and linker, polymethyl methacrylate (PMMA) is used as a polymer carrier, and anhydrous tetrahydrofuran (THF) is used as a solvent.

[0067] Among them, the molar ratio of LiNH2 and MgH2 is 2:1; the molar ratio of added Ca(BH4)2 is 10 mol% of the molar amount of MgH2; the amount of PMMA added is 5 wt% of the total mass of LiNH2-MgH2; the concentration of PMMA in anhydrous THF is 2 mg / ml.

[0068] The following steps were all carried out in an argon atmosphere:

[0069] (1) LiNH2, MgH2 and Ca(BH4)2 powders were mixed and mixed with steel balls at a ball-to-powder ratio of 80. The rotation speed was 250 rpm and the ball milling time was 24 h to obtain LMNH powder mixed with Ca(BH4)2, which was recorded as LMNH-CB.

[0070] (2) Prepare an anhydrous THF solution of PMMA at the above concentration and stir at 250 rpm at room temperature for 3 h to obtain a polymer solution.

[0071] (3) The LMNH-CB powder was slowly added to the polymer solution to form a solid-liquid mixed slurry. The mixed slurry was stirred for 3 h under the same conditions. After the stirring, the slurry was aged at room temperature for 12 h.

[0072] (4) The aged mixed slurry was vacuum dried at 90 °C for 12 h to obtain the final product PMMA@LMNH-CB.

[0073] Example 2

[0074] LiNH2 and MgH2 are used as raw materials, lithium borohydride (LiBH4) is used as a catalyst and linker, polycarbonate (PC) is used as a polymer carrier, and anhydrous THF is used as a solvent.

[0075] Among them, the molar ratio of LiNH2 and MgH2 is 8:3; the molar ratio of added LiBH4 is 7 mol% of the molar amount of MgH2; the amount of PC added is 4 wt% of the total mass of LiNH2-MgH2; and the concentration of PC in anhydrous THF is 30 mg / ml.

[0076] The following steps were all carried out in an argon atmosphere:

[0077] (1) LiNH2, MgH2 and lithium borohydride powders were mixed and mixed with steel balls at a ball-to-material ratio of 60. The rotation speed was 300 rpm and the ball milling time was 16 hours to obtain LMNH powder mixed with lithium borohydride, which was recorded as LMNH-LB.

[0078] (2) Prepare a PC anhydrous THF solution according to the above concentration and stir at 300 rpm at room temperature for 2 h to obtain a polymer solution.

[0079] (3) The LMNH-LB powder was slowly added to the polymer solution to form a solid-liquid mixed slurry, and the mixed slurry was stirred for 3 h under the same conditions. After the stirring, the slurry was aged at room temperature for 24 h.

[0080] (4) The aged mixed slurry was vacuum dried at 85 °C for 14 h to obtain the final product PC@LMNH-LB.

[0081] Example 3

[0082] LiNH2 and MgH2 are used as raw materials, LiLa(BH4)3Cl is used as a catalyst and linker, polymethyl methacrylate (PMMA) is used as a polymer carrier, and anhydrous THF is used as a solvent.

[0083] Among them, the molar ratio of LiNH2 and MgH2 is 2:1; the molar ratio of added LiLa(BH4)3Cl is 7 mol% of the molar amount of MgH2; the amount of PMMA added is 4 wt% of the total mass of LiNH2-MgH2; the concentration of PMMA in anhydrous THF is 2 mg / ml.

[0084] The following steps were all carried out in an argon atmosphere:

[0085] (1) LiNH2, MgH2 and LiLa(BH4)3Cl powders were mixed and mixed with steel balls at a ball-to-powder ratio of 100. The rotation speed was 350 rpm and the ball milling time was 15 h to obtain LMNH powder mixed with LiLa(BH4)3Cl, which was recorded as LMNH-LAB.

[0086] (2) Prepare an anhydrous THF solution of PMMA at the above concentration and stir at 400 rpm at room temperature for 1 h to obtain a polymer solution.

[0087] (3) The LMNH-LAB powder was slowly added to the polymer solution to form a solid-liquid mixed slurry. The mixed slurry was stirred for 2 h under the same conditions. After the stirring, the slurry was aged at room temperature for 48 h.

[0088] (4) The aged mixed slurry was vacuum dried at 80°C for 20 h to obtain the final product PMMA@LMNH-LAB.

[0089] The structures of the products prepared in Example 1, Example 2 and Example 3 were tested by X-ray diffraction (XRD) technology. The test results are as follows: Figures 1 to 3 As shown, the spectrum of LMNH is obtained from the test of pure LMNH (referring to lithium magnesium nitrogen hydrogen material without doping substrate and adding catalyst). The results show that the structure of polymer-coated LMNH composite material is consistent with pure LMNH, and the characteristic peaks are mainly MgH2 and LiNH2. There are no characteristic peaks of oxides such as MgO in the composite material, indicating that the addition of borohydride and the coating process did not cause LMNH oxidation. At the same time, no characteristic peaks of borohydride are shown in the composite material, which is because the amount of borohydride added is extremely low. This shows that the synthesis process and the interaction between catalyst and polymer do not affect the structure of LMNH and do not cause oxidation of the final product.

[0090] The chemical groups and chemical bonds in the sample of Example 1 were characterized by Fourier transform infrared spectroscopy (FTIR). Figure 4 and Figure 5 As shown, the horizontal axis is the wave number and the vertical axis is the relative transmittance, where Figure 5 yes Figure 4 At wave number 1315 -1 -1415 cm -1 A zoomed-in display of the range map. The chemical groups corresponding to the characteristic peaks are shown in Table 1 below.

[0091] Table 1

[0092] <![CDATA[Wavenumber (cm -1 )]]> Chemical Bond 839 C=O deformation vibration 894-971 PMMA main chain CC vibration 1090 BH bending vibration 1150-1170,1300 PMMA ester bond CO vibration 1368,1377 <![CDATA[Vibration of -CH3 in B-OCH3 and ester bond]]> 1446,1472 <![CDATA[Asymmetric bending of PMMA C-CH3 & C-CH2]]> 2342,2360 BH Stretching

[0093] Table 1 lists the main infrared absorption bands in PMMA@LMNH-CB and their corresponding chemical groups and chemical bonds. -1 The characteristic absorption peak corresponds to the BO bond formed between the B element in Ca(BH4)2 and the O element in -O-CH3 in PMMA, proving that a chemical link is indeed formed between the borohydride dispersed in LMNH in Example 1 and the PMMA coating LMNH.

[0094] The chemical groups and chemical bonds in the samples of Example 2 and Example 3 were characterized by Fourier transform infrared spectroscopy (FTIR). Figure 6 and Figure 7 As shown, Figure 6 and Figure 7 There are inner images, that is, the dotted box part is enlarged and displayed at the position indicated by the arrow. The relationship between the inner image and the large image is shown in Figure 5 and Figure 4 Only the chemical bonds related to borohydride are marked in the spectrum, and both are shown at 1368cm -1The BO bond is formed between the B element in the borohydride and the O element in the -O-CH3 of the ester group in the polymer, proving that the composite materials using different borohydrides and ester-containing polymers have the same bond connection effect, verifying that the B element in the borohydride can form a BO bond with the O element in the ester group of the polymer.

[0095] The material's hydrogen absorption and desorption kinetics and cycle stability were tested using a high-temperature and high-pressure gas adsorption instrument (PCT). The equipment used was a French Setram PCT Pro fully automatic siverts high-pressure gas absorption and desorption analyzer. The hydrogen absorption and desorption kinetics test temperatures were 175°C and 190°C, the hydrogen absorption pressure was 80 bar hydrogen pressure, and the hydrogen desorption pressure was 1 bar hydrogen pressure; the cycle stability test conditions were 160°C, the hydrogen absorption pressure was 80 bar hydrogen pressure, the hydrogen desorption pressure was 1 bar hydrogen pressure, and the number of cycles was 10 times. The test temperature for pure LMNH material was 190°C, the hydrogen absorption and desorption pressures were the same, and the number of cycles was 5 times.

[0096] Taking PC@LMNH-LB in Example 2 as an example, its hydrogen absorption and desorption kinetics at 175°C were tested, and compared with the hydrogen absorption and desorption kinetics of PC@LMNH (PC directly loaded with LMNH, the coating steps were also S2 and S3, but no borohydride was mixed, and the loading amount was 4wt%) at 175°C, and PC@LMNH-KH (KH was used as a catalyst, the KH addition amount was 7mol%, the coating steps were also S1-S3, but the borohydride was replaced by KH, and the PC loading amount was 4wt%) at 175°C and 190°C.

[0097] from Figure 8 and Fig. 9 The results show that the hydrogen absorption and desorption kinetics of the LMNH composite material catalyzed by LiBH4 are significantly improved. At a lower temperature (175°C), its hydrogen absorption and desorption rate and capacity are significantly better than other materials (PC@LMNH, PC@LMNH-KH).

[0098] from Figures 10 to 13 The results show that borohydride as a catalyst can greatly improve the kinetic performance of LMNH. The reversible hydrogen storage capacity of the composite materials of Examples 1 to 3 under lower reaction conditions, i.e., 160°C, is ≥4.0wt%, which is equivalent to that of pure LMNH at 190°C. The performance stability of pure LMNH material is poor. After only 5 cycles, its hydrogen desorption capacity decreases from 4.4wt% to 3.8wt%, a decay of about 14%. The hydrogen desorption capacity retention rates of PMMA@LMNH-CB, PC@LMNH-LB, and PMMA@LMNH-LAB after 10 cycles are 98.8%, 93.8%, and 98.6%, respectively, and the stability is significantly improved.

[0099] It can be seen from the examples that the use of about 4wt%-5wt% of a polymer containing an ester group as a coating material can improve the hydrogen absorption and desorption stability of the composite material. The reason is that the oxygen element in the ester group can form a chemical bond with the boron element in the borohydride doped into the LMNH as a catalyst, thereby promoting the uniform coating of the polymer on the surface of the LMNH containing the borohydride. In the case where no chemical link is formed, it is often necessary to use a high content of polymer as a coating material to achieve a comprehensive coating effect on the LMNH particles. For example, the use of TPP as a coating material has been reported in the literature. [7] TPX [8] 、PVA [9] When coated with polymers such as LMNH, the incorporation amounts reached 20wt%, 25wt%, and 60wt%, respectively. Under high loading, TPP@LMNH, TPX@LMNH, and PVA@LMNH showed good cycle stability, with a capacity retention rate of about 98% remaining in 4 cycles, 20 cycles, and 50 cycles, respectively. However, due to the negative impact of this high loading, the hydrogen storage capacity of the TPP@LMNH composite material dropped to about 3.8wt%, and PVA@LMNH further dropped to 2.1wt%. In the present invention, due to the advantage of chemical linkage, the polymer can be coated on the surface of LMNH in a more uniform manner, thereby reducing the amount of polymer used and preserving the hydrogen storage capacity of the composite material. As can be seen in the embodiment, the hydrogen storage capacity of the composite material is still ≥4.0wt% under 160°C.

[0100] In general, the present invention proposes a lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage and a preparation method thereof. The material composition includes: lithium or magnesium amide, lithium or magnesium hydride, borohydride which is also a catalyst and a linker for connecting the external polymer shell, and a polymer carrier containing an ester group as the external shell. The material structure includes from the inside to the outside: a LMNH core layer containing uniformly dispersed borohydride, and a polymer shell uniformly covering the core layer. The preparation process used uses the borohydride uniformly dispersed in the LMNH as a chemical linker to connect the polymer shell coated on the surface, and forms a BO bond through the interaction between the B element and the O element of the -OR ester group in the polymer. On the one hand, the B element is evenly distributed on the surface of LMNH, so the polymer containing ester groups that forms BO bonds with B will also be evenly distributed on the surface of LMNH. This chemical link can make a small amount of polymer evenly distributed on the surface of LMNH, prolong its hydrogen absorption and desorption cycle life, and at the same time try to avoid the negative impact of the addition of polymer on the hydrogen storage capacity of LMNH composite materials; on the other hand, the polymer shell is tightly connected to the LMNH surface due to the BO bond, and there will be no problems such as displacement during repeated hydrogen absorption and desorption caused by ordinary physical deposition.

[0101] In the description of this specification, the description with reference to the terms "one embodiment", "certain embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0102] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

[0103] References:

[0104] [1]Liu, Y.; Zhong, K.; Luo, K.; Gao, M.; Pan, H.; Wang, QJ Am.Chem. Soc. 2009, 131, 1862.

[0105] [2] Wang, J. Liu, T. Wu, G. Li, W. Liu, Y. Araujo, C. Scheicher, R.Blomqvist, A. Ahuja, R. Xiong, Z. Yang, P. Gao, M. Pan, H. Chen, P., Angew.Chem., Int. Ed. 2009, 48, 5828.

[0106] [3] Li, C. Liu, Y. Ma, R. Zhang, X. Li, Y. Gao, M. Pan, H., ACS Appl.Mater. Interfaces, 2014, 6(19):17024-17033.

[0107] [4] RR Shahi, RK Mishra, V. Shukla, A. Bhatnagar and ONSrivastava, Int. J. Hydrogen Energ., 2017, 42, 29350-29359.

[0108] [5] Y. Chen, P. Wang, C. Liu and HM Cheng, Int. J. HydrogenEnerg., 2007, 32, 1262.

[0109] [6] Xia, G. Tan, Y. Chen, X. Sun, D. Guo, Z. Liu, H. Uoyang, L. Zhu,M. You, X. Adv. Mater., 2015, 27(39): 5981-5988.

[0110] [7] Wang, J.; Hu, J.; Liu, Y.; Xiong, Z.; Wu, G.; Pan, H.; Chen, PJ Mater. Fabric. 2009, 19, 2141.

[0111] [8] Cao H, Georgopanos P, Capurso G, Pistidda C, Weigelt F, ChaudharyA, Filiz V, Tseng J, Wharmby M, Dornheim M, Abetz V, Klassen T. Mater. TodayEnergy, 2018, 10, 98.

[0112] [9] Xia, G.; Chen, X.; Zhao, Y.; Li, X.; Guo, Z.; Jensen, C.; Gu, Q.;Yu, X. ACS Appl. Mater. Interfaces 2017, 9, 15502.

[0113]

[10] Xia, G.; Tan, Y.; Li, D.; Guo, Z.; Liu, H.; Liu, Z.; Yu, X. Sci.Rep. 2014, 4, 6599.

[0114]

[11] Xia, G.; Chen, X.; Zhou, C.; Zhang, C.; Li, D.; Gu, Q.; Guo, Z.;Liu, H.; Liu, Z.; Yu, XJ Mater. Fabric. A 2015, 3, 12646.

Claims

1. A lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage, comprising a core layer and a polymer shell layer, characterized in that: The raw materials of the core layer include metal hydride, metal amide and borohydride. In a protective atmosphere, the metal hydride, metal amide and borohydride are mixed and ball-milled to obtain the core layer. The metal ion of one of the metal hydride and the metal amide is lithium, and the metal ion of the other is magnesium. The polymer shell layer is a polymer containing an ester group; the molar ratio of Mg to Li in the metal hydride and the metal amide is 1:2 or 3:8; in the raw materials of the core layer, the amount of the borohydride used is 1%-15% of the total amount of magnesium in the metal hydride and the metal amide, based on the amount of substance; the particle size range of the core layer is 10nm-2000nm, and the mass of the polymer shell layer is 2%-15% of the mass of the core layer.

2. The lithium magnesium nitrogen hydrogen material coated by polymer chemical linking according to claim 1, characterized in that: The mass of the polymer shell layer is 3%-7% of the total mass of the metal hydride and the metal amide.

3. The lithium magnesium nitrogen hydrogen material coated by polymer chemical linking according to claim 1, characterized in that: Listed chemical compounds selected: LiBH4, KBH4, NaBH4, Be(BH4)2, Mg(BH4)2, Ca(BH4)2, Al(BH4)3, Li K(BH4)2, LiY(BH4)4, NaY(BH4)4, LiZn2(BH4)5, NaZn2(BH4)5, Li3MZn5(BH4) 15 , KZn(BH4)Cl2, NaY(BH4)Cl2, LiX(BH4)3Cl, LiLa(BH4)3Br, LiLa(BH4)3I, Li(BH4) 1-x Q x , Na(BH4) 1-x Q x , K(BH4) 1-x Q x , Ca((BH4) 1- x Q x )2, Li2(BH4)(NH2), Li4(BH4)(NH2)3, Na2(BH4)(NH2), Mg(BH4)(NH2), A(BH4) g •nNH3, LiMg(BH4)3•nNH3, Li2Mg(BH4)4•nNH3, Li2Al(BH4)5•nNH3, LiSc(BH4)4•nNH3, Li2Mn(BH4)4•nNH3, Li2Fe(BH4)5•nNH3 or NaZn(BH4)3•nNH3; Where: 0<x<1; M=Mg or Mn; X=La, Ce, Pr, Nd, Sm or Gd; Q=Cl, Br or I; A=Li, Mg, Ca, Sr, Al, V, Cr, Mn, Fe, Co, Zn, Y, Zr, La, Ce, Gd or Dy, g value is equal to the valence of the corresponding metal ion of A; n=1, 2, 3, 4, 5 or 6.

4. The lithium magnesium nitrogen hydrogen material coated by polymer chemical linking according to claim 1, characterized in that: The material of the polymer shell layer is selected from at least one of polymethyl methacrylate, polycarbonate, polycaprolactone, polyurethane, polyethylene terephthalate, polybutylene terephthalate, polyphenylene terephthalate-butylene terephthalate, and polylactic acid polyester.

5. The lithium magnesium nitrogen hydrogen material coated by polymer chemical linking according to claim 1, characterized in that: The material of the polymer shell layer is selected from composite polymers containing ester structures on polymer chain segments.

6. The lithium magnesium nitrogen hydrogen material coated by polymer chemical linking according to claim 4 or 5, characterized in that: The molecular weight of the material of the polymer shell layer ranges from 20,000 to 500,000.

7. A method for preparing a lithium magnesium nitrogen hydrogen material coated by polymer chemical linking, characterized in that: The following steps are involved: In a protective atmosphere, a metal hydride, a metal amide and a borohydride are mixed and ball-milled to obtain a core layer; the metal ion of one of the metal hydride and the metal amide is lithium, and the metal ion of the other is magnesium; based on the amount of substance, the molar ratio of Mg to Li in the metal hydride and the metal amide is 1:2 or 3:8, and the amount of the borohydride is 1%-15% of the total amount of magnesium in the metal hydride and the metal amide; In a protective atmosphere, a polymer containing an ester group is added to an organic solvent to prepare a completely dissolved polymer solution; Adding the core layer to the polymer solution, stirring and aging, and then volatilizing in a vacuum environment to remove the organic solvent, to obtain the lithium magnesium nitrogen hydrogen material coated with polymer chemical linkage; The particle size of the core layer ranges from 10 nm to 2000 nm, and the mass of the polymer shell layer is 2% to 15% of the mass of the core layer.

8. The method for preparing a lithium magnesium nitrogen hydrogen material coated by polymer chemical linking according to claim 7, characterized in that: The organic solvent is selected from methanol, ethanol, propanol, isopropanol, butanol, isobutanol, cyclopentanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 4-methylcyclohexanol, glycerol, benzyl alcohol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, methyl ether, ethyl ether, ethylene oxide, 1,2-propylene oxide, 1,2-butylene oxide, tetrahydrofuran, 2-methylfuran, 3-methylfuran, 2, 5-dimethylfuran, 2-methyltetrahydrofuran, acetone, methylacetone, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylpropionamide, N,N-dimethylacetamide, N-ethylacetamide, 2-pyrrolidone, N-methylpyrrolidone, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, butylcyclohexane, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, diethylbenzene, dichloromethane, chloroform or carbon tetrachloride.

9. The method for preparing a lithium magnesium nitrogen hydrogen material coated by polymer chemical linking according to claim 7, characterized in that: The concentration of the polymer solution is 5 mg / ml-100 mg / ml.

Citation Information

Patent Citations

  • Preparation method of composite hydride hydrogen storage material and composite hydride hydrogen storage material

    CN107915203A

  • Polymer-coated hydrogen storage material, preparation method and application thereof

    CN112390224A